2016
DOI: 10.1016/j.jml.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Shared and distinct mechanisms in deriving linguistic enrichment

Abstract: a b s t r a c tMeanings of basic expressions can be enriched by considering what the speaker could have said, but chose not to, that is, the alternatives. We report three priming experiments that test whether there are shared enrichment mechanisms across a diverse range of linguistic categories. We find that quantifier, number, and ad hoc enrichments exhibit robust priming within their categories and between each other. Plural enrichments, in contrast, demonstrate within-category priming but no between-categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 60 publications
1
76
1
Order By: Relevance
“…Second, rates of strong interpretations were higher following strong and alternative prime trials than weak primes, as shown by the main effect of prime, F(2, 186) = 32.24, p < .001. Planned comparisons showed that rates of implicature were significantly higher following strong primes than weak primes, t(99) = 6.67, p < .001, illustrating the basic priming effect observed by Bott and Chemla (2016). There was also significantly greater rates of implicature following alternative primes than weak primes, t(99) = 6.69, p < .001.…”
Section: Analysis and Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Second, rates of strong interpretations were higher following strong and alternative prime trials than weak primes, as shown by the main effect of prime, F(2, 186) = 32.24, p < .001. Planned comparisons showed that rates of implicature were significantly higher following strong primes than weak primes, t(99) = 6.67, p < .001, illustrating the basic priming effect observed by Bott and Chemla (2016). There was also significantly greater rates of implicature following alternative primes than weak primes, t(99) = 6.69, p < .001.…”
Section: Analysis and Discussionmentioning
confidence: 84%
“…While this theory relates to processing cost, and not implicature rates, it nonetheless suggests that alternative salience is important for adult processing of implicatures. Bott and Chemla (2016) also argued that the salience of the alternative was important. They tested whether people could be primed to derive scalar implicatures, in the same way that they can be primed to produce particular syntactic structures (e.g., Bock, 1986;Bock, Dell, Chang, & Onishi, 2007;Branigan, Pickering, & Cleland, 2000;Thothathiri & Snedeker, 2008;see Pickering & Ferreira, 2008 for a review).…”
Section: Alternatives In Scalar Implicaturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have taken a step toward addressing these questions by testing generalization of pragmatic infelicity across lexical items (Bott & Chemla, ; Pogue, Kurumada, & Tanenhaus, ). Pogue et al () first exposed listeners to two speakers who gave instructions in displays where scalar adjectives were necessary (e.g., a display with a large and a small chair, and two unrelated items).…”
Section: Discussionmentioning
confidence: 99%